2017
DOI: 10.1007/s13205-017-0913-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity of chitosan–lysozyme nanoparticles on the growth, membrane integrity, and β-1,3-glucanase production by Aspergillus parasiticus

Abstract: Synthesis of nanocomposites from antimicrobial biopolymers such as chitosan (CS) and lysozyme (LZ) is an important and promising area in bionanotechnology. Chitosan-lysozyme (CS-LZ) nanoparticles (NPs) were prepared by the nanoprecipitation method, using commercial chitosan of 153 kDa. TEM and dynamic light scattering (DLS) analysis were carried out to evaluate the morphology, size, dispersion, and Z potential. Association efficiency of lysozyme was determined using Coomassie blue assay. The antifungal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…With advances in research, antifungal mechanisms of lysozyme have been elucidated 46 48 . In addition to its enzyme activity and cationic nature, studies have shown that the loss of mitochondrial membrane potential, the exposure of phosphatidylserine in the outer leaflets of the cell membrane, chromatin condensation, and DNA damage may all be factors in how lysozyme affects the structure and death of fungi 47 , 49 . By incubating lysozyme with cell lines, we found that the extracellular fluid after incubation did not exhibit a nucleic acid inhibitory effect, while the intracellular fluid had nucleic acid inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in research, antifungal mechanisms of lysozyme have been elucidated 46 48 . In addition to its enzyme activity and cationic nature, studies have shown that the loss of mitochondrial membrane potential, the exposure of phosphatidylserine in the outer leaflets of the cell membrane, chromatin condensation, and DNA damage may all be factors in how lysozyme affects the structure and death of fungi 47 , 49 . By incubating lysozyme with cell lines, we found that the extracellular fluid after incubation did not exhibit a nucleic acid inhibitory effect, while the intracellular fluid had nucleic acid inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…2′,7′-Dichlorodihydrofluorescein diacetate (2,7-DCFH 2 -DA) is a nonfluorescent cell-permeable dye that is hydrolyzed intracellularly to its polar but nonfluorescent form DCFH 2 , on the action of cellular esterase enzymes and thus is retained in the cell. Oxidation of DCFH 2 by the action of intracellular reactive oxygen species (ROS) and other peroxides turns the molecule into its highly fluorescent form (DCF) that can be detected by various fluorescent methods . Considering this mentioned, the 2,7-DCFH 2 -DA dye was employed according to the methodology of Rajneesh Pathak et al, with some modifications. , Two drops of a 5 μM solution of 2,7-DCFH 2 -DA were added to each well, and the plates were incubated for 1 h under refrigeration in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of chitosan concentration 1 and 5 mg mL -1 in potato dextrose agar (PDA) medium showed 100% inhibition rate, while the diameter colony of control was 20.5 mm after five days incubation. On the other hand, chitosan only gives 40% spore viability of Aspergillus parasiticus, whereas control with 100% spore viability (Hernández-téllez et al 2017).…”
Section: Introductionmentioning
confidence: 94%